SYNTHESIS AND ANTIOXIDANT CAPACITY OF (CHLOROBENZYLIDENE)HYDRAZINYL-THIAZOLES - Adriana GROZAV; Daniela HANGANU; Ovidiu CRIȘAN; Dan Ioan PORUMB; Castelia CRISTEA (Studia Universitatis Babes-Bolyai Chemia, 2019)
2-(chlorobenzilidene)hydrazinyl-thiazole derivatives were conveniently prepared by Hantzsch reaction protocol, starting with thiosemicarbazone and ethyl 2-bromo-3-oxo-3-phenylpropanoate. Their antioxidant capacity was screened by electron transfer based assays. The results of both DPPH (1,1-Diphenyl-2-picrylhydrazyl) free radical scavenging, as well as Ferric Ion Reducing Antioxidant Power (FRAP) assay, indicated antioxidant capacity for the tested hydrazone derivatives. At the concentration of 9.5 µg/mL, the DPPH radical scavenging activity of ethyl 2-(2-(3-chlorobenzylidene)hydrazinyl)-4-phenylthiazole-5-carboxylate was found to be more than 93%.